Higher visceral adiposity is associated with an enhanced early thermogenic response to carbohydrate-rich food. Issue 2 (April 2016) - Gepner, Yftach; Bril, Nitzan; Shelef, Ilan; Schwarzfuchs, Dan; Serfaty, Dana; Rein, Michal; Cohen, Noa; Shemesh, Elad; Tangi-Rosental, Osnat; Sarusi, Benjamin; Goshen, Eyal; Kenigsbuch, Shira; et al.
Summary: Background: Studies examining the dynamics of the thermic effect of feeding (TEF) of specific food items and the relationship of TEF to visceral adiposity are limited. Methods: We measured resting energy expenditure (REE) and early-TEF (40-min postprandial, e-TEF) after 8-h fast by indirect calorimetry in 40 obese men, and imaged abdominal fat tissues by magnetic resonance imaging. Each participant was examined on two occasions, 3-weeks apart. At each examination we measured fasting REE and then postprandial REE following the isocaloric [∼380 kcal] consumption of either 56 gr walnuts [(8% carbohydrates; 84% fat, of which 72% polyunsaturated fat)], or 5-slices (150gr) of whole-grain bread (48% carbohydrates; 32% fat). e-TEF was calculated as the area under the curve between the fasting and postprandial tests. Results: Participants had a mean age of 45 ± 8 years, body-mass-index (BMI) = 31.1 ± 3.8 kg/m 2, total abdominal fat area = 901.4 ± 240 cm 2, visceral fat area (VAT) = 260 ± 102.9 cm 2, fasting REE = 1854 ± 205 kcal, REE/kg = 19.39 ± 1.73 kcal/kg, and respiratory quotient (RQ, CO2 eliminated /O2 consumed ) = 0.82 ± 0.04. Individuals who exhibited increased e-TEF (top ΔAUC median) to bread had higher VAT (299 cm 2 vs. 223 cm 2 ; p = 0.024) and higher BMI (32.4 kg/m 2 vs. 30.0 kg/m 2 ; p = 0.013), compared to their peers with the lower e-TEF response (ΔAUC below median). As expected, postprandial e-TEF was higher after whole-grain bread consumption [ΔAUC = +14 kcal/40min] compared to walnuts [ΔAUC = −2 kcal/40 min; p < 0.001]. Conclusions: Higher early thermic effect of high-carbohydrate food, likely reflecting digestion, early absorption and/or sympathetic tone (rather than metabolic utilization (oxidation)), associates with visceral adiposity. Future studies are required to determine if this association represents an added causality between early carbohydrate processing and visceral fat accumulation.